A multidimensional valuation of the human perception of construction vibration - Noviyanti, A A; Woodcock, J S (Journal of physics. Conference series, 2018)
Previous studies have shown that annoyance due to vibration does not simply depend on the magnitude of vibration exposure. However, only little is known about the important features that contribute the human perception of vibration. This paper presents a study investigating seated subjects' perception of construction induced groundborne vibration in the vertical direction with the method of multidimensional scaling. The investigation was conducted using a paired comparison subjective test. Sixteen subjects were asked about their perception of the annoyance and similarity of sixty-six pairs of vibration stimuli. Through non-metric multidimensional scaling analysis, it is presented that the perception of construction vibration activities are dependent on up to three perceptual dimensions: duration of the signal, vibration energy in the 31.5 Hz of ⅓ octave band, and the centre of mass of the frequency spectrum of the signals. A regression model was built from the relationship between the annoyance ratings and the objective descriptors revealed through the multidimensional scaling analysis. This model was found to describe 79% of the variance in the measured perceived annoyance ratings data with p-level < 0.01.